2005
DOI: 10.1007/s00190-004-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

On the double-peak spectrum of the Chandler wobble

Abstract: Abstract.It is well known that two close spectral peaks with comparable amplitudes exist in the Chandler wobble (CW) band in the observed polar motion spectrum during the first half of the past century. However, it is not generally accepted that the CW is an oscillation with two closely lying frequencies, and some authors attribute the appearance of these two peaks to some unusual phase variation (180• shift) of the CW during 1920s-1930s. In this note, the phase variation of the CW is explored using the longes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…For the Chandler wobble to keep going, the energy associated with this motion should be replenished constantly and should have a stochastic part sufficient to cause the irregularities of this mode (Jeffreys, 1940). It was also proposed (see Guo et al, 2005) that the Chandler oscillation is a double frequency mode or that a widespread annual excitation causes its irregularities. We shall not consider this hypothesis here.…”
Section: Introductionmentioning
confidence: 96%
“…For the Chandler wobble to keep going, the energy associated with this motion should be replenished constantly and should have a stochastic part sufficient to cause the irregularities of this mode (Jeffreys, 1940). It was also proposed (see Guo et al, 2005) that the Chandler oscillation is a double frequency mode or that a widespread annual excitation causes its irregularities. We shall not consider this hypothesis here.…”
Section: Introductionmentioning
confidence: 96%
“…For example, the double peak of Chandler wobble spectrum has been analysed whether it is one or two close by frequency oscillations. In the work of Guo et al (2005) this is discussed in detail and it's concluded, that we should wait until 2030-th, when, in case of dual components, Chandler oscillations should decrease, as in 1930-th. Though, as it can be seen from Figure 2b there is a tendency of Chandler component to decrease in the last decade, we still supposed in our study, that there is one resonance frequency, what can be physically derived from the theory of the Earth's rotation, as it was developed in works of Euler, Liouville, Poincare and others.…”
Section: Discussionmentioning
confidence: 99%
“…Per the thought experiment above, this is the reason why the observed Chandler wobble appears to be amplitude-modulated and phase-modulated, which in effect explains why the observed Chandler wobble appears to be of multi-frequency (cf. Chao, 1983;Guo et al, 2005). Conversely, de-convolution of the observed Chandler wobble off its free motion reveals the excitation function.…”
Section: "Thought Experiment" Revisitedmentioning
confidence: 93%